Making Creative Videos as Learning Media - Sahirin, Rahmat; Cian, Lung; Wang, Yuanyuan; Zou, Guijiao (Journal International Inspire Education Technology, 2023)
This article is the development of several field studies that researchers have summarized. This research was conducted for the process of making learning media into creative videos through the use of the Canva application. Learning media is needed by an educator to facilitate the teaching and learning process in schools through the material taught. Usually, in teaching material, the teacher will use many books according to the government-provided ones. Various methods will also be used to teach students in supporting the teaching and learning process. One application that is easy to use & used in making videos as a learning medium is the Canva application. This application is online based, the contents of which provide exciting features, designs, templates and so on. By using the Canva application, teachers can develop skills materials for students so that the media used can be utilized in academic life.